Reduce hyperactive behavior on children with Attention Deficit Hyperteactivity Disorder through kinetic sand play therapy - Indah Prawesti (Caring : Jurnal Keperawatan, 2021)
Attention Deficit Hyperactivity Disorder (ADHD) is a disorder characterized by an inability to maintain attention, regulate activity levels and control impulsive behavior. According to the Centers for Disease Control and Prevention in 2017, people with ADHD are increasing by 5% each year. One of the therapies method that can be given to ADHD children is play therapy. Play therapy is used as a way to help ADHD children communicate their ideas and feelings. One of play therapy that is easy to do is to use kinetic sand. The aims of this study is to determine the reduction of hyperactive behavior in children with ADHD using kinetic sand play therapy. The methode of this study is descriptive quantitative research with the case study method apllied in this study. The population were children with ADHD who shown hyperactive behavior and received a sample of six children. The measuring instrument used is the Indonesian Hyperactivity Child Behavior Assessment Scale and univariate analysis was carried out. The characteristics of the respondents were mostly aged 9 – 12 years (50%) and based on gender the most were boy (83,3%). The mean score of hyperactivity before kinetic sand play therapy was 38,8 and after intervention was 31,7, so the difference mean score of hyperactivity was 7,1. There is a decrease in hyperactive behavior in children with ADHD after kinetic sand play therapy